An overview of breast cancer: classification and related signaling pathways - Chan, Pit Foong; Abd Hamid @ Abdul Razak, Roslida (HH Publisher, 2021)
The burden of cancer continues to grow in developed and developing countries, with about 70% of all cancer mortality in low- and middle-income countries. Among different cancer types, breast cancer is recognized as one of the five most common causes of death in cancer in women worldwide, right after lung cancer. Histological classification divides breast tumors into different categories based on their behavior and clinical outcome. However, the histological classification system has some limitations, thus molecular subtype classification has been studied extensively to improve the classification system for breast cancer. Like any other cancers, several signaling pathways that enhance the proliferation, survival, invasion, and metastasis capability of tumor cells have been observed in breast cancer. These crucial signaling pathways contributing to the etiology of breast cancer include breast tumor kinase (BRK) pathway, Notch signaling, Nuclear Factor-kappaB (NF-κB) pathway, and human epidermal growth factor receptor (HER) pathway. In the present review article, we summarize our current understanding of breast cancer and its signaling pathways, which serve as basic information on tumor formation, maintenance, and expansion that could help form better breast cancer management in patients.